2010
DOI: 10.3109/00016480903559731
|View full text |Cite
|
Sign up to set email alerts
|

Do patients with sclerotic mastoids require aeration to improve success of tympanoplasty?

Abstract: Tympanic membrane perforation closure was successful in 76.1% (n = 35) of the 46 patients undergoing myringoplasty and in 78.3% (n = 36) of the 46 patients undergoing myringoplasty with mastoidectomy. The difference between the closure rates of the two groups was not statistically significant (p > 0.05). The difference between the two groups for hearing gain was also not statistically significant (p > 0.05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
43
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 15 publications
5
43
1
4
Order By: Relevance
“…Studies have shown that the infection condition of the middle ear, the morphology of the tympanic mucosa and blockage of the middle ear cleft could all affect tympanic membrane transplantation and tympanoplasty [14]. Toros et al [9] conducted a retrospective comparison of the reconstruction of the tympanic membrane with or without mastoidectomy in 92 patients with sclerotic mastoids. The results showed that there was no difference in hearing improvement or tympanic membrane reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the infection condition of the middle ear, the morphology of the tympanic mucosa and blockage of the middle ear cleft could all affect tympanic membrane transplantation and tympanoplasty [14]. Toros et al [9] conducted a retrospective comparison of the reconstruction of the tympanic membrane with or without mastoidectomy in 92 patients with sclerotic mastoids. The results showed that there was no difference in hearing improvement or tympanic membrane reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between the two groups for hearing gain was also not statistically significant (p>0.05). 11 Mishiro et al also supported the use of tympanoplasty without mastoidectomy in chronic non-cholesteatomatous otitis media with an equivalent rate of grafting success and hearing results regardless of the state of the ear at repair (draining vs. nondraining) or the addition of a mastoidectomy. This was supported by Ryner Jose C stating that although mastoidectomy may be done on simple TM perforations there was no clear advantage for its routine practice in CSOM in absence of active infection or disease.…”
Section: Discussionmentioning
confidence: 95%
“…However, they also asserted that especially in cases scheduled for only myringoplasty, its added benefits, potential risks and cost-effectiveness should be meticulously evaluated. [13] In our clinics, we routinely obtain temporal bone CTs for all patients with detected COM for the last 20 months. We perform tympanomastoidectomy through an postauricular approach in cases with available computed tomographic evidence favouring cholesteatoma in the middle ear or mastoid bone.…”
Section: Discussionmentioning
confidence: 99%